POLITIK OLAHRAGA DI SULAWESI TENGAH (1946-1964) - Rizal, Syamsu; Sadi, Haliadi; Humaedi, Humaedi (Katalogis, 2021)
The problem of this article was that Central Sulawesi Province was formed in 1964, but before that, it had participated in PON IV Makassar in 1957 and PON V Bandung in 1961. This article aims first, to explain the political conditions in Central Sulawesi from NIT period until the formation of Central North Sulawesi Province in 1960. Second, to explain the participation of Central Sulawesi in PON IV Makassar 1957 and PON V Bandung 1961. Third, to analyze the relationship between Central Sulawesi's participation in PON IV and PON V Bandung, with the politics of the effort, namely the formation of Central Sulawesi Province. This article used historical methods with sociological and political approaches. The results show that the struggle for the formation of Central Sulawesi Province was marked by the participation of Central Sulawesi in PON IV Makassar in 1957 and PON V Bandung in 1961. This article concludes that sports are a means of struggle for the formation of Central Sulawesi Province.Â